Features of physical training of internal affairs officers for the prosecution and detention of criminals - Troyan E.I.; Minulin R.M. (Theory and Practice of Physical Culture, 2025)
Introduction. Physical training of employees of internal affairs bodies is aimed at achieving a high level of development of professionally significant physical qualities of employees, mastery of combat fighting techniques [1]. In educational institutions of the Russian Ministry of Internal Affairs system, as part of the implementation of the main programs of professional training for individuals hired for the first time by the internal affairs bodies for the position of "Policeman", training sessions on physical training on the topic of "Combat training practice and tactics of using combat fighting techniques" are provided. In this regard, there was a need to find effective means and methods for training employees of internal affairs agencies to pursue and detain criminals [2]. Purpose of the research – identification of effective means and methods of physical training of employees of internal affairs agencies for the pursuit and detention of criminals. Research methodology and organization. The study was organized at the Tyumen Institute for Advanced Training of the Ministry of Internal Affairs Employees in 2024. The following scientific methods were used in the course of the study: analysis of the practice of actions of employees of internal affairs bodies in situations of pursuit and detention of criminals; analysis of regulatory and legal documents governing the physical training of employees of internal affairs bodies, educational and methodological support for the physical training of employees of the Ministry of Internal Affairs of Russia; systematization of the means and methods used for the physical training of employees of internal affairs bodies. Results and its discussion. As a result of the research, educational and methodological support was prepared for the educational topic “Educational and combat practice and tactics of using combat fighting techniques”. This training topic was integrated into the thematic plan of the main program of professional training for the professional preparation of persons for the position of "Police Officer". The staff examines in detail the techniques and tactics of pursuing and detaining a criminal, performing techniques, issues of interaction and mutual assistance of staff in defending against attacks and in detaining criminals. Algorithm for modeling training situational tasks for the use of combat fighting techniques according to the scheme: “search – pursuit – restriction of the assistant’s freedom of movement”. Conclusion. The developed educational topic "Training and combat practice and tactics of using combat techniques" can be used in the educational process of physical training in educational institutions of the Russian Ministry of Internal Affairs system; Professional training centers of the Russian Ministry of Internal Affairs, as well as within the framework of professional service and physical training of the personnel of the Internal Affairs Bodies.